High performance liquid chromatography network based automated data acquisition system for pharmaceutical research applications / Mohammad Shukri Hapeez - Hapeez, Mohammad Shukri (2011)
Sharing an experimental result of chromatography process is very crucial in pharmaceutical research industries, where large amount of result need to be obtained. The chromatography data are saved into its owned exclusive file format and the file is unable to be read without the proprietary software application, in addition, the data are not sharable. Saving the experimental results in format that can be read by any common computer application is important and storing the file which can be shared by other users is very important where data and information are kept and shared digitally. The automated acquisition method presented in this thesis, is to provide an alternative in obtaining chromatography data in open source format which can be read without using the proprietary software and the chromatography data can be shared. Automated Acquisition Chromatogram System (AMCOS) has been developed to allowing users save the experimental results from the HPLC instrument in an open source format. Chromatogram Online System (CONSYS) has been developed as the centralized database system where other users can share the stored chromatography data and the outcome of this work is to have the obtained chromatograms in an open source format and shared the obtained chromatogram by other users.